2019
DOI: 10.1111/jan.14086
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing decisions of mental health professionals to release service users from seclusion: A qualitative study

Abstract: Aim:This study aims to explore and understand factors influencing the decisions of mental health professionals releasing service users from seclusion.Background: Seclusion should only be used as a last resort and for the minimum possible duration. Current evidence outlines which service users are more likely to be secluded, why and what influences professionals' decision to seclude. Little is known about factors professionals consider when releasing service users.Design: A qualitative study was undertaken to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Patients and staff may both experience trauma because of seclusion (Krieger et al 2020) yet there is little known about their perspectives on the effects of seclusion both on them and on patients. Nevertheless, staff support the use of seclusion, in particular for patients who are aggressive or violent because they see no alternative to protect other patients, themselves, and the patient being secluded (Jackson et al 2019;Krieger et al 2020;Power et al 2020). Most data on these staff opinions come from surveys of staff working with adults.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients and staff may both experience trauma because of seclusion (Krieger et al 2020) yet there is little known about their perspectives on the effects of seclusion both on them and on patients. Nevertheless, staff support the use of seclusion, in particular for patients who are aggressive or violent because they see no alternative to protect other patients, themselves, and the patient being secluded (Jackson et al 2019;Krieger et al 2020;Power et al 2020). Most data on these staff opinions come from surveys of staff working with adults.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, staff support the use of seclusion, in particular for patients who are aggressive or violent because they see no alternative to protect other patients, themselves, and the patient being secluded (Jackson et al . 2019; Krieger et al . 2020; Power et al .…”
Section: Introductionmentioning
confidence: 99%
“…In terms of staffing factors, there is evidence that staffing levels and confidence within a team affect decision-making in terms of initiating and terminating seclusion. [15][16][17] Staffing levelsparticularly of senior stafftend to be reduced out of hours, and seclusion episodes that are initiated during the weekend tend to be longer, 18 so it is plausible that this would impact the success of seclusion termination. Given that medical staff have been viewed as having a distinctive role in the process of seclusion, 19 and the presence of a senior doctor is associated with the termination of seclusion, 18 we speculated that involving doctors in decision-making may also affect the success of seclusion termination.…”
mentioning
confidence: 99%
“…In terms of patient factors, qualitative research has suggested that ward staff place an emphasis on people cooperating with their care when deciding whether to terminate seclusion. 16 One of the more measurable manifestations of this is medication cooperation. Regarding psychopathology, aggression and agitation have been identified as being predictive of seclusion initiation.…”
mentioning
confidence: 99%